Semi-natural regeneration and conservation in agroforestry system models on small-scale farmers (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suryanto P, Sadono R, Yohanifa A, Widyawan MH, Alam T. 2021. Semi-natural regeneration and conservation in agroforestry system models on small-scale farmers. Biodiversitas 22: 858-865. The regeneration capacity can provide an overview of the abundance of species so that it can be used to determine the potential and opportunities for the sustainability of agroforestry systems. The purpose of this study was to determine the capacity of semi-natural regeneration in agroforestry system models for small-scale farmers. The study was carried out in Banaran Sub-district, Playen District, Gunungkidul Regency, Special Province of Yogyakarta, Indonesia. The observation was conducted on plant diversity, floristic composition, and agroforestry contribution. The results showed that the mixed cropping (MC) model had a higher total of individuals and diversity compared to the trees along with border (TAB) model in the sapling and seedling level. The MC model was relatively shorter to the waiting time of harvesting compared to the TAB model. The MC models weakness was the relatively high competition and the lack of opportunities to growing annual crops. The TAB model had an advantage in developing annual crops in an agroforestry system, while longer in waiting time for harvesting perennial crops. This study recommends annual pruning in the MC model for optimal stand growth, while in the TAB model, it is the enrichment planting in sapling and seedling levels.
Keywords: Agroforestry, conservation, mixed cropping, regeneration, trees along border